The spirituality of effective public secondary school principals in Northern Mindanao - Tantoco, Nelson C., Fr. (Animo Repository, 2017)
This study explored the spirituality of selected effective principals of public secondary schools in Northern Mindanao. It was premised that these principals spirituality positively influenced their leadership practices. The multiple-case study procedure was employed. Three effective principals of different religious affiliations and ethnicities from Northern Mindanao were purposively chosen as case studies. Data were gathered primarily through in-depth interviews. Objectives were focused at drawing out their leadership practices, definition of spirituality and corresponding spiritual behavior and experiences, and description of the manifestations of spirituality in their leadership practices. The principals definitions of spirituality all clustered around themes on ones relationship with God and with others, and living a godly life, displaying spiritual values normally associated with godliness. Their description of spirituality also included spiritual exercises. One principals spiritual experiences revealed an aspect of spirituality not common to the rest relationship with nature. Moreover, all the principals acknowledged that spirituality plays an important role in their performance as educational leaders. The influence of spirituality in their leadership practices was shown by the matching of each principals spiritual practice with the corresponding general and specific leadership practice/s that it affects. The study concluded that effective public secondary school principals in Northern Mindanao primarily view spirituality in terms of relationships with God, with others, and with nature. They do spiritual exercises which enable them to view their principalship introspectively. They also embody other spiritual values related to leadership effectiveness and recognize and manifest the vital role of spirituality in their principalship, regardless of their religious affiliations or ethnicity.